Occurrence factors of emotional burnout syndrome among young employees - L. V. Tarabakina; E. V. Zvonova; V. A. Tarasova (Вестник университета)
The issue of studying the factors causing the syndrome of burnout is an acute one in modern psychological science. The problem of emotional burnout syndrome in young employees is considered by the authors within the framework of psychological safety paradigm. The results of a study of emotional burnout syndrome in specialists with work experience of up to three years have been described. To conduct the study, methods were used aimed at identifying the degree of expression of emotional burnout syndrome, as well as the characteristics of labor behavior and attitude to work. Differences in labor behavior and attitudes to work among specialists with varying degrees of emotional burnout syndrome have been revealed. The conversation with employees has allowed us to highlight the main reasons for the appearance ofprofessional deformation. Young employees have called the causes that ruin their lives, systematic overtime working, the lack of the ability to obtain full knowledge, as well as the lack of support from relatives and Mefs.